Dukungan Sosial dan Resiliensi Pada Remaja Pasca Kematian Orang Tua: Sebuah Kajian Literatur - Calsum, Astri Yani; Purwandari, Eny (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
Losing a parent due to death is a meaningful event and has a profound impact on adolescents. It often creates a sense of sadness, loss and ongoing trauma. The role of parents is very important in supporting the developmental stages of adolescents. This study uses the Systematic Literature Review (SLR) approach to evaluate the influence and relationship between social support and resilience in adolescents after the death of a parent. The data for analysis is obtained through Google Scholar, accessed through Publish or Perish (Pop) using the keywords "social support" "resilience" and "adolescents after the death of a parent" resulting in 6 sources of journal articles and scientific papers that are worthy and in accordance with the research topic for further analysis. The results of the literature analysis show that social support has a positive contribution to resilience in adolescents who experience the loss of a parent due to death. Forms of social support that play a role in increasing resilience in adolescents include support from family and peers which are formed through emotional support and their direct presence in accompanying adolescents during difficult times after the death of their parents. This study confirms that the greater the social support received, the higher the level of resilience of adolescents in adapting, continuing self-development and facing life with optimism after the death of parent and better mentalityKeywords - Adolescents, Death of Parents, Social support, Resilience.